Caribbean Report 18-07-1995 - Richards, Ken (anchor); Fenton, David (correspondent); Wilkinson, Harold (correspondent); Reynolds, Brian (interviewee); Fraser, Tony (correspondent); Maharaj, Ramesh (interviewee); Clarke, Ellis, Sir (interviewee); Norton, Michael (correspondent) (The British Broadcasting Corporation, 1995)
In this report: in Montserrat the residents attempt to cope with the threat of a possible natural disaster. David Fenton reports on how people are reacting to the eruption of Montserrat's volcano. Plans by the Venezuelan Armed Forces to mount an offensive against illegal miners could affect neighbouring Guyana. Police in St. Kitts/Nevis are optimistic about resolving a suspected case of arson which destroyed a building used as the constituency office for the Minister of Education and Labour. In Trinidad and Tobago, after two failed attempts, the government is now seeking to amend the constitution to have the Speaker removed from office. Elections in Haiti have received another setback with a planned re-run of the first round in some parts of the country now postponed to the 6th August. Following a meeting with leaders of the local voodoo religion, President Aristide unveiled plans to build a new voodoo temple. In cricket, Brian Lara's batting suffered a further blow when he was bowled by a part-time cricketer for a duck.
1. Headlines with Ken Richards (00:00-00:27)
2. An explosion at Montserrat's volcano put seismic experts on alert (00:28-03:24)
3. Fears that Guyana may see an influx of illegal miners being removed from Venezuela (03:25-05:45)
4. In St. Kitts, police explore a possible arson attack on the ruling party member's office (05:46-08:19)
Keywords: Volcanoes -- Montserrat; Natural disasters -- Montserrat; Montserrat -- Social conditions; Miners -- Venezuela; Miners -- Guyana -- Economic conditions; Gold mines and mining -- Guyana; Arson investigation -- Saint Kitts and Nevis; Police -- Saint Kitts and Nevis; Parliamentary practice -- Trinidad and Tobago; Constitutional law -- Trinidad and Tobago; Legislative bodies -- Trinidad and Tobago -- Presiding officers; Trinidad and Tobago -- Politics and government; Elections -- Corrupt practices -- Haiti; Democracy -- Haiti; Haiti -- Politics and government -- 1986-; Voodooism -- Haiti; Haiti -- Religion; Religion and politics -- Haiti; Cricket -- Batting; Cricket players -- West Indies